PENGARUH FINANCIAL LITERACY DAN LIFESTYLE TERHADAP FINANCIAL MANAGEMENT BEHAVIOR DENGAN SELF CONTROL SEBAGAI VARIABEL INTERVENING PADA GENERASI Z DI SURAKARTA - Suryani, Mareta Dwi; Sudarno, Sudarno (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2026)
This study aims to determine (1) the effect of financial literacy on financial management behavior in generation Z in Surakarta, (2) the effect of lifestyle on financial management behavior in generation Z in Surakarta, (3) the effect of self-control on financial management behavior in generation Z in Surakarta, (4) the effect of financial literacy on financial management behavior mediated by self-control in generation Z in Surakarta, (5) the effect of lifestyle on financial management behavior mediated by self-control in generation Z in Surakarta. This study is a descriptive quantitative study sourced from primary data, with a sample of 100 respondents. The sampling technique uses non-probability sampling with quota sampling. Data collection uses a questionnaire via Google Form. The validity test technique uses the product moment technique and the validity test uses the Conbach's alpha technique. Data analysis uses descriptive statistics, normality test, linearity test, multicollinearity test, heteroscedasticity test, path analysis, t-test and R2 test. The results of the study prove that (1) financial literacy has a positive and significant effect on financial management behavior in generation Z in Surakarta, (2) lifestyle has a positive and significant effect on financial management behavior in generation Z in Surakarta, (3) self-control has a positive and significant effect on financial management behavior in generation Z in Surakarta, (4) financial literacy has a positive and significant effect on financial management behavior in generation Z in Surakarta through self-control, (5) lifestyle has a positive and significant effect on financial management behavior in generation Z in Surakarta through self-control.